Straintronics with van der Waals materials - Feng Miao (Nature Portfolio, 2021)
Abstract With the outstanding mechanical properties, van der Waals (vdW) materials have attracted extensive attention in the research of straintronics in the past decade. In this perspective, we first review the recent progresses of the straintronics with vdW materials based on three different lattice deformation modes, i.e., in-plane strain, out-of-plane strain, and heterostrain. Then we discuss the current technique challenges in this field, and finally provide our perspectives on future research directions for both fundamental physics and electronic applications.